2004
DOI: 10.1111/j.1471-4159.2004.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid synthesis is decreased in neuronal tissue in a mouse model of Sandhoff disease

Abstract: Sandhoff disease is a progressive neurodegenerative disorder caused by mutations in the HEXB gene which encodes for the b-subunit of b-hexosaminidase A and B, resulting in ganglioside GM 2 accumulation in the brain. We now demonstrate that phospholipid metabolism is altered in both cultured neurons and in brain tissue from a mouse model of Sandhoff disease, the Hexb-/-mouse. Metabolic labelling using [methyl-14 C]choline and L-[3-3 H]serine demonstrated reduced incorporation of [methyl-14 C]choline into phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Statistical di¡erences for total lipid phosphate and PC between Hexb þ/þ and Hexb À/À mice are indicated (* p< 0.001) Table 1 GM 2 and GA 2 levels in Hexb lung tissue. GM 2 and GA 2 were quanti¢ed in lung tissue from 3-month-old (n ¼ 15) and 4-month-old (n ¼ 15) Hexb mice Hexb þ /þ Hexb À/À Hexb þ/þ Hexb À/À (3 months) (Bodennec et al 2002) and macrophages (Trajkovic-Bodennec et al 2004) from a model of Gaucher disease, and in brain tissue of Hexb À/À mice (Buccoliero et al 2004), changes were observed in phospholipid metabolism, suggesting a dynamic interplay between these two metabolic pathways. Irrespective of the mechanism, changes in surfactant and lung phospholipid levels are entirely consistent with the lung pathology observed in Sandho¡ and Niemann^Pick diseases and with that observed in other diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical di¡erences for total lipid phosphate and PC between Hexb þ/þ and Hexb À/À mice are indicated (* p< 0.001) Table 1 GM 2 and GA 2 levels in Hexb lung tissue. GM 2 and GA 2 were quanti¢ed in lung tissue from 3-month-old (n ¼ 15) and 4-month-old (n ¼ 15) Hexb mice Hexb þ /þ Hexb À/À Hexb þ/þ Hexb À/À (3 months) (Bodennec et al 2002) and macrophages (Trajkovic-Bodennec et al 2004) from a model of Gaucher disease, and in brain tissue of Hexb À/À mice (Buccoliero et al 2004), changes were observed in phospholipid metabolism, suggesting a dynamic interplay between these two metabolic pathways. Irrespective of the mechanism, changes in surfactant and lung phospholipid levels are entirely consistent with the lung pathology observed in Sandho¡ and Niemann^Pick diseases and with that observed in other diseases.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first demonstration of the relationship between the therapeutic effects of a treatment and imaging data obtained by IMS. As the contributions of lyso-GM2, phospholipids, and myelin-enriched lipids to the neuropathogenesis of glycosphingolipodosis was suggested (2,(54)(55)(56), multitarget validation by IMS for disease-related and therapeutic biomarkers including brain lipids will be very helpful for elucidation of the neuropathogenic mechanism in small animal disease models and monitoring combined drug therapy in preclinical studies. We anticipate that i.c.v.ERT and/or GT utilizing the modified HEXB will be subjected to preclinical studies and clinical trials leading to clinical applications for the treatment of TSD patients in the near future not only in high-risk Ashkenazi-Jewish patients, but also in non-Jewish populations worldwide.…”
Section: 9mentioning
confidence: 99%
“…For example, Gaucher disease cells accumulate glucosylceramide, which directly activates CCT and stimulates PC synthesis (95). In Sandhoff disease, an accumulation of ganglioside GM2 is associated with reduced CCT activity and PC mass in the brain (96). In both diseases, altered PC synthesis may contribute to the pathology (97).…”
Section: Tissue-specific Roles For Cctmentioning
confidence: 99%